2006
DOI: 10.1051/lait:2006009
|View full text |Cite
|
Sign up to set email alerts
|

Creation and quality characterization of processed cheeses derived mainly from Halloumi cheese

Abstract: -Four new types of processed cheese based on Halloumi cheese were produced. Each cheese had the same concentration of dry matter (53%) and fat in dry matter (65%), but the constituents (Halloumi cheese, Kopanisti cheese, strained yoghurt, butter, emulsifiers and water) differed in concentration. Significant statistical differences were noticed in the total protein, water-soluble protein, lactose, ash, pH, hardness, springiness, adhesiveness, cohesiveness, gumminess, chewiness and organoleptic characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…The reason for that could be the lower content of protein of carrot paste than that in the control cheese, also the presence of sugar which weak the network of cheese. These obtained results are in the same line with those of (Kaminarides et al, 2006) who revealed that ash and salt contents of the cheese blend increased the hardness of the resulting processed cheese, so the control cheese was harder than the carrot cheese.…”
Section: Resultssupporting
confidence: 90%
“…The reason for that could be the lower content of protein of carrot paste than that in the control cheese, also the presence of sugar which weak the network of cheese. These obtained results are in the same line with those of (Kaminarides et al, 2006) who revealed that ash and salt contents of the cheese blend increased the hardness of the resulting processed cheese, so the control cheese was harder than the carrot cheese.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, raising SRPP (20%) resulted in a tendency for an increase in firmness (Table 6). On the other side, Kaminarides et al (2006) found that increasing the Halloumi cheese, salt, and ash levels of the blend increased the resulting processed cheese's hardness. Besides, the textural parameters included chewiness and springiness were increased by increasing the levels of SRPP.…”
Section: Radical Scavenging Activity (Rsa %) Of Spreadable Processed mentioning
confidence: 97%
“…Similar Adda et al [27] stated that cheeses of higher fat content are more elastic. Kaminarides et al [28] reported that increasing the salt and ash contents increased the hardness of the processed cheese. Korish and Abd-Elhamid [29] mentioned that the lowest values of hardness, springiness and chewiness in Kareish cheese, might be a result of the increase in cheese moisture content.…”
Section: Resultsmentioning
confidence: 99%